Burnout, depression, anxiety and insomnia among medical staff during the COVID-19 epidemic in Shanghai - Tang, Lin; Yu, Xin-tong; Wu, Yu-wei; Zhao, Na; Liang, Rui-long; Gao, Xiao-lin; Jiang, Wen-yan; Chen, Yun-fei; Yang, Wen-jia (Frontiers in Public Health, 2023)
BACKGROUND: Coronavirus disease 2019 (COVID-19) has progressively impacted our daily lives, resulting in unexpected physical and mental stress on medical staff. This study is designed to investigate the levels of and risk factors for burnout, depression, anxiety, and insomnia among medical staff during the COVID-19 epidemic breakout in Shanghai, China. METHODS: This cross-sectional survey was conducted from May 1 to May 31, 2022, among medical staff who were on the frontline during the epidemic breakout in Shanghai from different institutions. The MBI-HSS was used to assess burnout, PHQ-9, GAD-7 and ISI were used to evaluate mental status and insomnia. RESULTS: A total of 543 valid questionnaires were collected. The depersonalization, depression, anxiety, and insomnia scores of medical staff were significantly higher during the pandemic in Shanghai compared with norms, while lack of personal achievement scores were decreased. Working time, work unit, work environment and age are important influencers of burnout, depression and anxiety of medical staff. Long working hours are the most likely causes of burnout and emotional disorders. Medical staff in primary hospitals were most likely to suffer from burnout and emotional disorders, while medical staff in tertiary hospitals had a reduced sense of personal achievement. Young medical staff are prone to negative emotions such as depression and anxiety, while older medical staff have a lower sense of personal accomplishment. Medical staff who were not in the shelter hospitals or designated hospitals were more likely to have problems of emotional exhaustion, depersonalization and anxiety than those who were in the shelter hospitals or designated hospitals. Contracting COVID-19 had no effect on medical staff. Emotional exhaustion and depersonalization were positively correlated with anxiety, depression, and sleep disorders while personal achievement was negatively correlated with these factors. CONCLUSION: Medical staff in Shanghai had high burnout, depression, anxiety and insomnia levels during the epidemic outbreak in Shanghai. During the COVID-19, medical staff may suffer different psychological problems which should be concerned. Care and supports about burnout, mental health and insomnia need to be taken to promote the mental health of medical staff according to different characteristics of medical staff.